Religioisity in Animated Videos (Quantitative Content Analysis of the Upin and Ipin Animated Show) - Monika Pretty Aprilia; Rivga Agusta; Arselly Dwi Cahyani (Rekam : Jurnal Fotografi, Televisi, Animasi, 2022)
The animated children show Upin & Ipin is a popular show in Indonesia that contains many messages that can be a learned by Indonesian children. One of the issues most often carried in the Upin and Ipin show is religiosity, which is raised through worship activities, celebrations of religious holidays, and running daily life in accordance with the teachings of Islam. This study sees the concept of Glock and Stark's religious religion which is divided into five dimensions. The five dimensions are ritual dimension, intellectual dimension, ideology dimension, experimental dimension, and consequence dimension. The method used is quantitative content analysis. The results showed that the ritual dimensions that appeared were the biggest, then the intellectual dimensions and consequence dimensions were also emerged in a smaller percentage. In the animation "Upin & Ipin" the ritual dimensions performed by the characters in daily life emerge in the form of prayer, fasting, adhan, ablution, praying, celebrating the holiday, and reciting. The intellectual dimension emerged with a scene of the residents of Kampung Durian Runtuh who attended religious study activities. While the consequence dimensions are described when the characters do good deeds to fellow human beings.